2003
DOI: 10.1289/ehp.6058
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor-mediated activity of particulate organic matter from the Paso del Norte airshed along the U.S.-Mexico border.

Abstract: In this study, we determined the biologic activity of dichloromethane-extracted particulate matter < 10 micro m in aerodynamic diameter (PM10) obtained from filters at three sites in the Paso del Norte airshed, which includes El Paso, Texas, USA; Juarez, Chihuahua, Mexico, and Sunland Park, New Mexico, USA. The extracts were rich in polycyclic aromatic hydrocarbons (PAHs) and had significant biologic activity, measured using two in vitro assay systems: ethoxyresorufin-(O-deethylase (EROD) induction and the ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The seasonal differences in the total PAH levels were not as pronounced as that for the inorganic compounds found in PM: the ranges were 10-24 and 9-16 ng/m 3 in cold-dry and in the warm-dry seasons, respectively. The average PAH concentration (18.9 ng/m 3 ) was comparable to the 0.3-51.9 ng/m 3 range reported for other regions, such as Santiago, Chile, and Flanders, Belgium [Arrieta et al, 2003;Du Four et al, 2004], but it was higher than the PAH levels reported for rural areas and for some of the US cities (ranging from 0-0.4 ng/m 3 ) [WHO, 2000]. High proportions of carcinogenic PAHs (53.3%-73.3%) were found for the PAHs detected in the PM organic extracts, and these PAHs may be partially responsible for the observed genotoxicity.…”
Section: Chemical Characteristics Of Pmsupporting
confidence: 80%
“…The seasonal differences in the total PAH levels were not as pronounced as that for the inorganic compounds found in PM: the ranges were 10-24 and 9-16 ng/m 3 in cold-dry and in the warm-dry seasons, respectively. The average PAH concentration (18.9 ng/m 3 ) was comparable to the 0.3-51.9 ng/m 3 range reported for other regions, such as Santiago, Chile, and Flanders, Belgium [Arrieta et al, 2003;Du Four et al, 2004], but it was higher than the PAH levels reported for rural areas and for some of the US cities (ranging from 0-0.4 ng/m 3 ) [WHO, 2000]. High proportions of carcinogenic PAHs (53.3%-73.3%) were found for the PAHs detected in the PM organic extracts, and these PAHs may be partially responsible for the observed genotoxicity.…”
Section: Chemical Characteristics Of Pmsupporting
confidence: 80%
“…Humans are exposed to complex mixtures of PAHs via the diet, air and skin contact (Rothman et al, 1993;Schoket, 1999;Scherer et al, 2000;Arrieta et al, 2003;Oh et al, 2005). Low concentrations of high-molecular-weight PAHs, such as benzo [a]pyrene, are found in diesel exhaust and higher levels are found in woodsmoke (Burchiel et al, 2005).…”
Section: (F) Complex Mixturesmentioning
confidence: 99%
“…Generally benzo[a]pyrene (BaP) is considered a human PAH carcinogenic activity marker (10,79,81). A number of these index rankings for the PAHs analyzed in this study are shown for comparison in Table 6 where it can be noted that the carcinogenicity tends toward the higher MW PAHs, although carcinogenicity peaks and then declines for MW >252.…”
Section: Pah Analysis and Comparisonsmentioning
confidence: 99%
“…While particulate matter (PM) exposures in El Paso are relatively low in contrast to most of the rest of the U.S., ubiquitous evening peaks in hourly PM 10 and PM 2.5 concentrations during still-air conditions (a four-fold increase over a few hour period) during winter months is particularly notable (7,8). Correspondingly, it has been shown that the risk of PM-induced mortality in El Paso is higher during still-air inversions than it is during sandstorms (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation